(untitled) (Materiali di Estetica. Terza serie, 2020)
In the poem the words narrate their attempt to make themselves understood and, in their expressiveness, become holds for a lyrical understanding. But to make this possible, the poet must “know” about them, about their nature; know their imprint, their character, their posture but above all understand, where they come from and from whom, as well as from what. It is necessary, as Antonio Porta said so many times, to “go to shop”, that is, to enter an operational scriptural workshop, where matter and material know how to be present together on the table of language and language, scattered and stacked among the tools of the profession that every poet should possess and know how to manage. The poet’s “job” is to dedicate time to the word, and the “task” of poetry is to give it back regenerated /reinvented from one’s mother tongue. Here the poetic language must become more adherent to what must be brought to light, to what it must show: to let other people see and seize. Thinking in a poem also means remaining connected to the “place of elaboration”, in that exact point where language is installed between the experience and its deciphering in word. In all this the word experiences the life that was deemed to be its own. It will repay what it has been given.